EL PERFIL DEL DOCENTE EN RELACION AL LOGRO DE LA CALIDAD DE EDUCACION EN EL COLEGIO PARTICULAR ''JERUSALEN'' DE LA CIUDAD DE MILAGRO EN EL PERIODO LECTIVO 2007-2008. - MARIA LUISA MARCA DOMINGUEZ (2008)
THE PROFILE OF THE TEACHER IN RELATION TO THE ACHIEVEMENT OF THE QUALITY OF EDUCATION IN THE PRIVATE SCHOOL ''JERUSALEN'' OF THE CITY OF MILAGRO IN THE 2007-2008 SCHOOL PERIOD.